Rent Seeking and Power Hierarchies: A Noncooperative Model of Network Formation with Antagonistic Links - Kenan Huremovic (Fondazione Eni Enrico Mattei (FEEM), 2014)
Network structure has a significant role in determining the outcomes of many socioeconomic relationships, including the antagonistic ones. In this paper we study a situation in which agents, embedded in a network, simultaneously play interrelated bilateral contest games with their neighbors. Interrelatedness of contests induces complex local and global network effects. We first characterize the equilibrium of a game on an arbitrary fixed network. Then we study a dynamic network formation model, introducing a novel but intuitive link formation protocol. As links represent antagonistic relationships, link formation is unilateral while link destruction is bilateral. A complete k-partite network is the unique stable network topology. As a result, the model provides a micro-foundation for the structural balance concept in social psychology, and the main results go in line with theoretical and empirical findings from other disciplines, including international relations, sociology and biology.
Keywords: D85; D74; 330; Network Formation; Structural Balance; Contest